Analisis Penggunaan Bekisting Konvensional, Baja dan Sistim Peri dari Segi Biaya pada Struktur Pier Konstruksi Ramp On/Off Jalan Tol - Hamonangan Girsang (Universitas Mercu Buana, 2023)
Formwork is a concrete mold reference or temporary structural element in the work of construction that also contributes to the cost of project implementation, several types of formworks are using in the construction works are conventional, steel, aluminum, peri-system, fiberglass, that’s will make their contribution in the implementation of concrete construction structures. the selection for use of the formwork method are important role in achieving the success of the structural work, especially in the terms of costing because it is necessary to do a thorough analysis related to the formwork material used and the method of implementation. This study aims to compare the costs of using polymer system peri formwork, conventional formwork, and steel plate formwork in pier structure construction work.This research was conducted using descriptive analysis method, the data obtained from various sources were then analyzed and used for the research process in comparing costs. The construction structure reviewed in this study is specifically the pier structure construction consisting of pilecap, column and pierhead.After analyzing the use of bakesting by reviewing of cost performance, the use of polymer system peri formwork materials required costs IDR 773,879,700,- and with conventional formwork materials required costs IDR 1,391,152,241,- and using steel formwork requires IDR 1,091,953,197,- thus the comparative price index the three formwork materials are 1: 1.8: 1.4.